Parent-Reported Health-Related Quality of Life of Pediatric Burn Patients 5 to 7 Years after Burn Injuries: A Multicenter Study - Spronk, Inge; Trommel, Nicole; Baartmans, Martin; Polinder, Suzanne; van Baar, Margriet; on behalf of the Burden of Burn Injuries Study Group (European Journal of Pediatric Surgery, 2022)
Background Pediatric burns significantly impact the short-term health-related quality of life (HRQL) of children. Knowledge regarding the long-term impact is scarce. We therefore evaluated the parent-reported HRQL in pediatric burn patients 5 to 7 years after burns.Methods We invited parents of eligible children admitted to a Dutch Burn Center between August 2011 and September 2012. This sample was enriched with children with severe burns (> 10% of total body surface area [TBSA] burned) admitted between January 2010 and March 2013. The EQ-5D was completed by parents 5 to 7 years postburn. Outcomes and predictive factors were studied and compared between children with minor/moderate and severe burns.Results We included 130 children (mean TBSA burned 7%): 102 children with mild/intermediate burns and 28 with severe burns. Mean EQ-5D summary was 0.96 and EQ visual analogue scale (VAS) 93.1. These outcomes were significantly better in children with minor/moderate burns (0.97; 94.4) compared with children with severe burns (0.93; 88.3) (p < 0.05). Nineteen percent of the children with minor/moderate burns and 43% of those with severe burns reported any problems. The most frequently reported problem was anxiety/depression for both groups. Pain/discomfort (p = 0.012) and cognition (p = 0.035) were statistically significantly worse in children with severe burns compared with those with minor/moderate burns. Full thickness burns and number of surgeries were found to predict long-term HRQL impairment.Conclusion Five to seven years postburn, the majority of children in our study (76%) did not experience long-term problems with HRQL. In a minority of the children, burns showed to have a prolonged negative impact, especially in those being severely burned and who had to undergo surgery for their burns. Most experienced problems were related to anxiety/depression. These important insights could be used to inform children and their parents about the expected long-term HRQL after pediatric burns.
Keywords: burn injuries; children; adolescents; health-related quality of life; proxy-reported outcomes